2016
DOI: 10.1002/anie.201511859
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Multidimensional Laplace NMR Using a Single‐Sided Magnet

Abstract: Laplace NMR (LNMR) consists of relaxation and diffusion measurements providing detailed information about molecular motion and interaction. Here we demonstrate that ultrafast single- and multidimensional LNMR experiments, based on spatial encoding, are viable with low-field, single-sided magnets with an inhomogeneous magnetic field. This approach shortens the experiment time by one to two orders of magnitude relative to traditional experiments, and increases the sensitivity per unit time by a factor of three. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…[18][19][20] and now the P2DRM, opens the possibility for investigation of time-sensitive processes. Recently, a novel single-scan version of the T 1 -T 2 correlation pulse sequence has been developed, where the T 1 kernel is encoded along the direction of an applied gradient during an adiabatic frequency sweep π pulse and then retrieved by Fourier transform of the echoes acquired under a read gradient [18,19]. However, a full T 1 -T 2 correlation measurement may not be necessary for porous media applications, and the P2DRM may offer a more simple interpretation by framing the results in terms of the utilized prior knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] and now the P2DRM, opens the possibility for investigation of time-sensitive processes. Recently, a novel single-scan version of the T 1 -T 2 correlation pulse sequence has been developed, where the T 1 kernel is encoded along the direction of an applied gradient during an adiabatic frequency sweep π pulse and then retrieved by Fourier transform of the echoes acquired under a read gradient [18,19]. However, a full T 1 -T 2 correlation measurement may not be necessary for porous media applications, and the P2DRM may offer a more simple interpretation by framing the results in terms of the utilized prior knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to UF‐PGSTE experiment, UF‐PGSE produces artifact‐free data with a single‐scan, providing significant prospects for monitoring fast processes in real time. Spatial encoding lowers the sensitivity of the experiment, typically by factor of four, but signal‐to‐noise ratio per unit time may be increased, because multiple scans can be collected in the experiment time of the conventional experiment . The single‐scan approach also enables one to use hyperpolarized substances to boost the sensitivity by several orders of magnitude, allowing the studies of samples with low concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial encoding lowers the sensitivity of the experiment, typically by factor of four, [38] but signal-to-noise ratio per unit time may be increased, because multiple scans can be collected in the experiment time of the conventional experiment. [38,42] The single-scan approach also enables one to use hyperpolarized substances to boost the sensitivity by several orders of magnitude, [38] allowing the studies of samples with low concentration. A rigorous theoretical analysis of the echo amplitude in UF-PGSE and UF-PGSTE experiment justified the theoretical basis of the methods and revealed that the conventional exponential fit to the experimental data leads to diffusion coefficient values overestimated by a few per cent.…”
Section: Discussionmentioning
confidence: 99%
“…, for the investigation of dynamics and physical environments of HP gases in porous media, both with high-field and low-field (mobile) NMR instruments. [236237] …”
Section: Remote-detection Mri Of Hyperpolarized Gasesmentioning
confidence: 99%